The Impact of Cryoballoon Versus Radiofrequency Ablation for Paroxysmal Atrial Fibrillation on Healthcare Utilization and Costs: An Economic Analysis From the FIRE AND ICE Trial. Issue 8 (27th July 2017) - Chun, K. R. Julian; Brugada, Josep; Elvan, Arif; Gellér, Laszlo; Busch, Matthias; Barrera, Alberto; Schilling, Richard J.; Reynolds, Matthew R.; Hokanson, Robert B.; Holbrook, Reece; Brown, Benedict; Schlüter, Michael; et al.
Abstract : Background: This study sought to assess payer costs following cryoballoon or radiofrequency current (RFC) catheter ablation of paroxysmal atrial fibrillation in the randomized FIRE AND ICE trial. Methods and Results: A trial period analysis of healthcare costs evaluated the impact of ablation modality (cryoballoon versus RFC) on differences in resource use and associated payer costs. Analyses were based on repeat interventions, rehospitalizations, and cardioversions during the trial, with unit costs based on 3 national healthcare systems (Germany [€], the United Kingdom [£], and the United States [ ]). Total payer costs were calculated by applying standard unit costs to hospital stays, using International Classification of Diseases, 10th Revision diagnoses and procedure codes that were mapped to country‐specific diagnosis‐related groups. Patients (N=750) randomized 1:1 to cryoballoon (n=374) or RFC (n=376) ablation were followed for a mean of 1.5 years. Resource use was lower in the cryoballoon than the RFC group (205 hospitalizations and/or interventions in 122 patients versus 268 events in 154 patients). The cost differences per patient in mean total payer costs during follow‐up were €640, £364, and 925 in favor of cryoballoon ablation ( P =0.012, 0.013, and 0.016, respectively). This resulted in trial period total cost savings of €245 000, £140 000, and 355 000. Conclusions: When compared with RFC ablation, cryoballoon ablation was associated with a reduction in resource use and payer costs. In all 3 national healthcare systems analyzed, this reduction resulted in substantial trial period cost savings, primarily attributable to fewer repeat ablations and a reduction in cardiovascular rehospitalizations with cryoballoon ablation. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Identifier: NCT01490814.